State of the Art in Pulmonary Arterial Hypertension: Molecular Basis, Imaging Modalities, and Right Heart Failure Treatment - Melika Shafeghat; Yasmin Raza; Roberta Catania; Amir Ali Rahsepar; Blair Tilkens; Michael J. Cuttica; Benjamin H. Freed; Jingbo Dai; You-Yang Zhao; James C. Carr (Biomedicines)
Pulmonary hypertension (PH) is broadly defined as a mean pulmonary arterial pressure (mPAP) exceeding 20 mm Hg at rest. Pulmonary arterial hypertension (PAH) is a specific subset of PH characterized by a normal pulmonary arterial wedge pressure (PAWP), combined with elevated mPAP and increased pulmonary vascular resistance (PVR), without other causes of pre-capillary hypertension such as lung diseases or chronic thromboembolic pulmonary hypertension. The majority of PAH cases are idiopathic; other common etiologies include connective tissue disease-associated PAH, congenital heart disease, and portopulmonary hypertension. To a lesser extent, genetic and familial forms of PAH can also occur. The pathophysiology of PAH involves the following four primary pathways: nitric oxide, endothelin-1, prostacyclin, and activin/bone morphogenetic protein (BMP). Dysregulation of these pathways leads to a progressive vasculopathy marked by vasoconstriction, vascular proliferation, elevated right heart afterload, and ultimately right-sided heart failure. Diagnosing PAH is challenging and often occurs at advanced stages. The gold standard for diagnosis remains invasive right heart catheterization. Along with invasive hemodynamic measurements, several noninvasive imaging modalities such as echocardiography and ventilation-perfusion scanning are key adjunct techniques. Also, recent advancements in cardiac magnetic resonance (CMR) have opened a new era for PAH management. Additionally, CMR and echocardiography not only enable diagnosis but also aid in evaluating disease severity and monitoring treatment responses. Current PAH treatments focus on targeting molecular pathways, reducing inflammation, and inhibiting right-sided heart failure. Integrating imaging with basic science techniques is crucial for enhanced patient diagnosis, and precision medicine is emerging as a key strategy in PAH management. Additionally, the incorporation of artificial intelligence into both molecular and imaging approaches holds significant potential. There is a growing need to integrate new imaging modalities with high resolution and reduced radiation exposure into clinical practice. In this review, we discuss the molecular pathways involved in PAH, the imaging modalities utilized for diagnosis and monitoring, and current targeted therapies. Advances in molecular understanding and imaging technologies, coupled with precision medicine, could hold promise in improving patient outcomes and revolutionizing the management of PAH patients.